2016
DOI: 10.15446/agron.colomb.v34n2.56799
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological aspects of fruit crops in the era of climate change. A review

Abstract: The increased concentration of carbon dioxide (CO2) and other greenhouse effect gases has led to global warming, which has resulted in climate change, increased levels of ultraviolet (UV) radiation and changes in the hydrological cycle, affecting the growth, development, production and quality of fruit crops, which undoubtedly will be difficult to predict and generalize because the physiological processes of plants are multidimensional. This review outlines how the effects of high/low solar radiation, temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 36 publications
3
49
0
3
Order By: Relevance
“…In this way, climate change has a direct effect on the growth, development, production and quality of agricultural products. However, in some cases, the response of plants to these conditions may be favorable, but at other times, the results may be negative, especially when there are extreme changes in the environment (Fischer et al 2016). Additionally, Wood et al (2000) report that in Latin America, about 11,3% of the areas potentially suitable for cultivation have poor drainage, because topography promotes waterlogging, high water levels and the presence of stagnant surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, climate change has a direct effect on the growth, development, production and quality of agricultural products. However, in some cases, the response of plants to these conditions may be favorable, but at other times, the results may be negative, especially when there are extreme changes in the environment (Fischer et al 2016). Additionally, Wood et al (2000) report that in Latin America, about 11,3% of the areas potentially suitable for cultivation have poor drainage, because topography promotes waterlogging, high water levels and the presence of stagnant surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis (source of carbohydrates production in plant species) and respiration are essential physiological processes for plant vegetative growth and their reproduction. These processes are directly influenced by climatic variables such as temperature, water (rainfall) and solar radiation (Fischer, Ramírez, & Casierra‐Posada, ), suggesting that spatiotemporal variation of these climatic variables could differently affect reproductive ability of plant species. The best reproductive potential responses in plant species are obtained in the cardinal range of climatic variables with specific species response (Fischer et al, ; Kumar, Rashid, Bhat, & Bhat, ).…”
Section: Discussionmentioning
confidence: 99%
“…From these results, it was concluded that the environmental condition including exposure to radiation, in direct or indirect method (water stress), affect promotion of floral bud differentiation, floral organ development, maturity of fruits and at the end affecting the growth, development, production and quality of fruit crops [88] [89] [90].…”
Section: E Alattar E Radwanmentioning
confidence: 99%